EDUCATIONAL TECHNLOGIES IN THE PROCESS OF TEACHING FOREIGN LANGUAGES - Tuychibaeva Shahnoza (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract. The article describes educational technologies applied in practice. Educational technology is a classic example of social technology and represents a relatively new trend in educational science. Educational technologies are associated with increasing the effectiveness of training and education and are aimed at the result of the educational process - the training of highly qualified specialists.